Grief is the thing with feathers - Porter, Max 1981- (Faber & Faber, 2015)
This title was shortlisted for The Goldsmiths Prize 2015. It was shortlisted for the Guardian First Book Award 2015. "Dazzlingly good...Anyone who has ever loved someone, or lost someone, or both, will be gripped by it. It's very sad and very funny." (Robert Macfarlane). "In this slyly funny and thrillingly original work, Max Porter somehow pulls a brand new story out of the darkest despair." (Jenny Offill). "I'm not sure I've read anything like Max Porter's book before. It stunned me, full of beauty, hilarity, and thick black darkness. It will stay with me for a very long time." (Evie Wyld). In a London flat, two young boys face the unbearable sadness of their mother's sudden death. Their father, a Ted Hughes scholar and scruffy romantic, imagines a future of well-meaning visitors and emptiness. In this moment of despair they are visited by Crow - antagonist, trickster, healer, babysitter. This sentimental bird is drawn to the grieving family and threatens to stay until they no longer need him. As weeks turn to months and the pain of loss gives way to memories, the little unit of three starts to heal. In this extraordinary debut - part novella, part polyphonic fable, part essay on grief - Max Porter's compassion and bravura style combine to dazzling effect. With full of unexpected humour and profound emotional truth, Grief Is the Thing with Feathers marks the arrival of a thrilling new talent.